(untitled) (Tabanque. Revista Pedagógica, 2024)
The review article is oriented towards the new horizons posed by the use of Artificial Intelligence systems in current (today’s) education, beginning with a historic- anthropological review of the school, from its inception as an institution in the industrial era to our time. Furthermore, it does an overview of the problems generated in subjectivity and intersubjectivity of the educational subjects and ponders the purpose of education and the affectation of the introduction of AI in the ecosystem. To conclude, the interaction between teaching and the and the aim of humanities in this hyper-technological context is reviewed.